Age- and sex-specific reference values for non-HDL cholesterol and remnant cholesterol derived from the Nordic Reference Interval Project (NORIP). (17th February 2019) - Ridefelt, Peter; Hagström, Emil; Svensson, Maria K.; Åkerfeldt, Torbjörn; Larsson, Anders
Abstract: Objectives : Non-HDL-cholesterol (non-HDL-C) has been reported to be a better marker of cardiovascular risk than LDL-cholesterol (LDL-C) especially in individuals with high triglyceride values. Further, levels of remnant cholesterol have been suggested to in part explain residual risk not captured with LDL-C. The aim of the present study was to define reference values for non-HDL-C and remnant cholesterol based on data from the Nordic Reference Interval Project (NORIP). Methods : We analyzed the test results for total cholesterol, HDL-cholesterol and triglycerides from 1392 healthy females and 1236 healthy males. Non-HDL-C was calculated as measured total cholesterol minus measured HDL-cholesterol. Remnant cholesterol was calculated using the Friedewald equation for LDL-C: measured total cholesterol minus measured HDL-cholesterol and minus calculated LDL-cholesterol. The 2.5th and 97.5th percentiles for these markers were calculated according to the International Federation of Clinical Chemistry guidelines on the statistical treatment of reference values. Results : Age (18–<30, 30–49 and ≥50 years) and sex-specific reference intervals were calculated for non-HDL-cholesterol and remnant-cholesterol. Levels of non-HDL-C and remnant cholesterol differed between sex and age strata. Conclusions : Age- and sex-specific reference intervals should be used for the triglyceride rich lipid variables non-HDL-C and remnant cholesterol. Since these markers may add information on risk burden beyond LDL-C, our hope is that these reference intervals will aid the introduction of automatic reporting of non-HDL-C by hospital laboratories.